Information overload, anxiety, stress, and depression of online distance learners - Masrek, Mohamad Noorman; Baharuddin, Mohammad Fazli; Jalil, Abdurrahman; Aman, Fadhilah (International Journal of Evaluation and Research in Education (IJERE), 2024)
In the ever-expanding landscape of online education, the mental well-being of online distant learners has emerged as a critical concern. This study delves into the complex interplay between information overload, stress, anxiety, and depression among online distant learners in Malaysian universities. Using a survey research method and utilizing perceptual measures, we explored the psychological states of online distant learners in Malaysia. Based on the analysis of 384 responses, the results showed that online distant learners did not report experiencing information overload, stress, anxiety, or depression. Despite this absence, the study identified significant positive associations between information overload and stress, information overload and anxiety, as well as between stress and anxiety, and anxiety and depression. The implications of this study resonate profoundly in the realm of online education policy-making and implementation.